Seroprevalence of foot and mouth disease (FMD) among sedentary cattle in northern Plateau, Nigeria (Asian Journal of Medical and Biological Research, 2015)
This study was aimed to determine the seroprevalence of foot and mouth disease (FMD) in cattle and identifying the potential risk factors associated with the disease among sedentary cattle in northern part of Plateau state, Nigeria. Two hundred and seventy cattle aged from 6 months to ?3 years old were randomly selected and identified and whole blood collected from the jugular vein using plain evacuated tubes. Whole blood was processed and separated and sera were screened for foot and mouth disease virus (FMDV) 3D non-structural proteins using blocking enzyme linked immunosorbent assay (ELISA). Overall, 55.9% (95%CI: 49.96-61.77) FMD seroprevalence was obtained from the study area. Seroprevalence was highest in Riyom (82.5%), followed by Barkin Ladi (66.2%), Jos South (55.5%) and Bassa (41.2%) (x2 = 17.21, P